Caracterização físico-química dos óleos-resinas de copaifera multijuga hayne e avaliação da variabilidade química de sua fração volátil - Silva, Marcos Túlio da (2016)
The genus Copaifera it belongs to the family Fabaceae, this genus it has 72 species distributed in tropical regions of America and West Africa. In Brazil there are 16 endemic species, highlighting: Copaifera officinalis L., Copaifera reticulata Ducke, Copaifera multijuga Hayne, Copaifera confertiflora Benth., Copaifera langsdorffi Desf., Copaifera coriacea Mart. and Copaifera cearensis Huber ex Ducke, as the most studied. Of The trunk of Copaiferas extracted an oil-resin which is attributed anti-inflammatory actions, antimicrobial, healing ulcers and wounds in general. In the chemical composition of copaiba oil-resin stand out a volatile fraction mainly composed of sesquiterpene and sesquiterpene hydrocarbons and oxygenates a resinous fraction consisting of diterpene acids. The lack of effective parameters to characterize and therefore realize the quality control, linked to the intrinsic chemical variability of oil-resin undertake the commercialization of this raw material for pharmaceutical industry. Among the most studied species, the Copaifera multijuga Hayne, known as copaíba, mari mari, purple copaíba, is used for its anti-inflammatory properties and was the subject of this study this work. This study aimed to characterize oils-resins of C. multijuga through physical and chemical methods, aiming at quality control parameters. The Chapter 1 presents the chemical variability of the essential oil obtained from 11 specimens of oil-resin of C.multijuga collected in Santarém / Pará, analyzed by GC-MS; analysis of physical parameters (density, refractive index and viscosity) and chemical (identification and quantification of β-caryophyllene marker HPLC) in the oils-resins samples, essential oil analysis from oil-resin as well as the isolation and identification of diterpenes in a sample oil-resin of C. multijuga. The density and the refractive index remained constant while the viscosity ranged between specimens. The β-caryophyllene content identified and quantified by HPLC ranged from 22.4 to 75.1%. In the essential oil, the major compounds were β-caryophyllene, the α-humuleno and multivariate statistical analyzes grouped the 11 specimens in two clusters in relation to compounds, δ-elemene, α-copaene, β-caryophyllene, α-humuleno, trans-cadina-1(6),4-diene and trans-4-muurola(14),5-diene. Statistical analysis realized out showed a high chemical variability between individuals of the same species of C. multijuga even the samples have been collected close to each other and in the same period of year. The diterpenes isolates of oil-resin of C. multijuga were the copalic acid, 3-hydroxy-copalic, 3-acetoxy-copalic and ent-agático.